2019
DOI: 10.1038/s41598-019-48331-w
|View full text |Cite
|
Sign up to set email alerts
|

Berberine improved experimental chronic colitis by regulating interferon-γ- and IL-17A-producing lamina propria CD4+ T cells through AMPK activation

Abstract: The herbal medicine berberine (BBR) has been recently shown to be an AMP-activated protein kinase (AMPK) productive activator with various properties that induce anti-inflammatory responses. We investigated the effects of BBR on the mechanisms of mucosal CD4 + T cell activation in vitro and on the inflammatory responses in T cell transfer mouse models of inflammatory bowel disease (IBD). We examined the favorable effects of BBR in vitro , usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 48 publications
3
45
0
Order By: Relevance
“…Disturbance of such tight junctions gives rise to further inflammatory reactions and oversecretions of chemokines and adhesive molecules [ 28 ]. Additionally, elevated levels of inflammatory cytokines exaggerate the innate and acquired immune reactions, involving activation of inflammatory CD4 + T cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbance of such tight junctions gives rise to further inflammatory reactions and oversecretions of chemokines and adhesive molecules [ 28 ]. Additionally, elevated levels of inflammatory cytokines exaggerate the innate and acquired immune reactions, involving activation of inflammatory CD4 + T cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 11 ] stated that BER restored the intestinal barrier function in experimental colitis induced by dextran sodium sulfate in mice through upregulation of expression of tight junction proteins (zonula occluden-1, occludin, and epithelial cadherin) in colonic tissue. Further, BER exhibited noteworthy suppression of the UC-associated inflammatory response on lamina propria CD4 + T cells via activation of AMP-activated protein kinase and inhibition of oxidative phosphorylation [ 29 ]. In the present study, treatment of rats with BER significantly alleviated the colonic inflammation due to suppression of overproduction of MPO and inflammatory cytokines such as TNF- α , IL-1 β , and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested that berberine possessed numerous pharmacological activities, including anti-microbial, anti-diabetic, anti-colorectal cancer, analgesic, lipid modulatory, anti-depressant, and blood glucose and anti-inflammatory effects 21 . Particularly, berberine has been suggested to function as an effective agent in treating experimental colitis, including UC and CD, which were largely due to the role of berberine in modulating gut microbiota, neurogenic inflammation, mucosal immunity, and barrier function 20,[22][23][24] . Though the underlying mechanism of berberine has been focused on activation of adenosine 5′-monophosphate (AMP)activated protein kinase (AMPK) 23 , we revealed a new molecular mechanism of berberine in attenuating chronic UC.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrastis canadensis is a natural plant with a long history of use, and berberine is considered its most effective ingredient [ 20 ]. It has been confirmed that Hydrastis canadensis can ameliorate several pathological statuses and has anti-inflammation [ 35 ], anti-cancer [ 36 ], anti-diabetic [ 37 ], anti-obesity, and anti-hyperlipidemia properties [ 38 , 39 ], in addition to offering myocardial protection [ 40 ]. Our results indicate that laying hens fed with diets containing goldenseal root, leaf, or a mixture of leaf and root (1:1) showed no mortality throughout the experiments.…”
Section: Discussionmentioning
confidence: 99%